2023
DOI: 10.3389/fpls.2023.1181173
|View full text |Cite
|
Sign up to set email alerts
|

Identification and functional characterization of a flavonol synthase gene from sweet potato [Ipomoea batatas (L.) Lam.]

Meng Kou,
Chen Li,
Weihan Song
et al.

Abstract: Flavonol synthase (FLS) is a key enzyme of the flavonoid biosynthetic pathway, which catalyzes the conversion of dihydroflavonols into flavonols. In this study, the FLS gene IbFLS1 was cloned and characterized from sweet potato. The resulting IbFLS1 protein showed a high similarity with other plant FLSs. The conserved amino acids (HxDxnH motifs) binding ferrous iron and residues (RxS motifs) binding 2-oxoglutarate were found in IbFLS1 at conserved positions, as in other FLSs, suggesting that IbFLS1 belongs to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Flavonol synthase (FLS) is the key committed enzyme in the biosynthesis of class flavonols, which convert dihydroflavonols to the form of quercetin, kaempferol, and myricetin (Kou et al 2023). Considering the high accumulation (the relative intensity, number of top accumulated metabolites, and total accumulated metabolites) of flavonols, the upregulation of gene FLS (Supplementary file 1, Supplementary file 9) suggested a redirection of metabolic flux into the flavonols branching pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Flavonol synthase (FLS) is the key committed enzyme in the biosynthesis of class flavonols, which convert dihydroflavonols to the form of quercetin, kaempferol, and myricetin (Kou et al 2023). Considering the high accumulation (the relative intensity, number of top accumulated metabolites, and total accumulated metabolites) of flavonols, the upregulation of gene FLS (Supplementary file 1, Supplementary file 9) suggested a redirection of metabolic flux into the flavonols branching pathway.…”
Section: Discussionmentioning
confidence: 99%
“…It has an important effect on anthocyanin accumulation [ 30 ]. Many FLS genes have been cloned and identified in other plants [ 31 ]. In the present research, it was found that FLSs are involved in the synthesis of many flavonoids and were significantly upregulated according to the DEG analysis of the transcriptome.…”
Section: Discussionmentioning
confidence: 99%
“…Our analysis and enzyme assay data from previous studies suggest that FLS sequences within the first dicot subclade (Fagales I, Sapindales I, Malpighiales I, and Malvales I) display a pronounced substrate specificity for DHK. In contrast, FLS sequences within the second dicot subclade show a preference for both DHK and DHQ and may have a higher specificity for DHQ (63,65,66,103,105,114,128). ANS/LDOX, which catalyses the immediate step downstream of DFR, is closely related to FLS and shows 50-60% protein sequence similarity.…”
Section: Functional Divergence During Fls Evolutionmentioning
confidence: 99%
“…This suggests a gene duplication during the evolution of land plants probably before the split of the aforementioned orders followed by a significant divergence in FLS sequences in these orders due to functional requirements, leading to the formation of distinct FLS clades. Within the Malvales order, including cotton species, an additional duplication event was observed, originating from FLS H duplication, followed by a subsequent substitution leading to the re-emergence of FLS Y (H132Y In contrast, FLS sequences within the second dicot subclade show a preference for both DHK and DHQ and may have a higher specificity for DHQ (98,100,112,113,125,126,130).…”
Section: Functional Divergence During Fls Evolutionmentioning
confidence: 99%
See 1 more Smart Citation